GODELIER, Maurice. Les tribus dans l’histoire et face aux États, Paris, CNRS Éditions, 2010, 86 pp. - Villas Boas Filho, Orlando (Revista de Antropologia, 2013)
GODELIER, Maurice. Les tribus dans l’histoire et face aux États, Paris, CNRS Éditions, 2010, 86 pp.